Latest Changes in the Content and Copy Writing of Online Marketing: Examining the evolution of content and copywriting in online marketing (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In today's information-rich, digital environment, content marketing has become a veryeffective strategy. While not a novel tactic, content marketing is increasingly being used by businessesof all sizes. Why then has content marketing become so popular in the modern world? This paperdiscusses the latest changes in the content and copywriting of online marketing.